Delocalization of exciton and electron wavefunction in non-fullerene acceptor molecules enables efficient organic solar cells - Guichuan Zhang (Nature Portfolio, 2020)
Y6, as a non-fullerene acceptor for organic solar cells, has attracted intensive attention because of the low voltage loss and high charge generation efficiency. Here, Zhang et al. find that the delocalization of exciton and electron wavefunction due to strong π-π packing of Y6 is the key for the high performance.